The Role of Teachers as Facilitators in Learning to Foster a Sense of Responsibility and Independence in Fourth-Grade Students at SD Muhammadiyah 4 Kandangsapi - Naila Rosyada; Arief Cahyo Utomo (FKIP - Universitas Riau, 2026)
Character education plays a vital role in shaping students who are not only academically excellent but also possess strong moral values and good character. This study aims to examine the role of teachers as facilitators in fostering a sense of responsibility and independence among fourth-grade students at SD Muhammadiyah 4 Kandangsapi, as well as to identify the challenges encountered in this process. This study employs a qualitative approach using a descriptive research design and a case study methodology. The research subjects include fourth-grade teachers, students, and the school principal, selected through purposive sampling. Data collection techniques included observation, interviews, and documentation. Data validity was tested through source triangulation and methodological triangulation, while data analysis utilized an interactive analysis model encompassing data reduction, data presentation, and the drawing of conclusions and verification. The results of the study indicate that the teacher’s role as a facilitator in fostering the character traits of responsibility and independence is carried out through the establishment of routine activities, the enforcement of classroom rules, providing students with opportunities for active participation, and guidance during the learning process. The character trait of responsibility is evident in students’ readiness to learn and their ability to complete tasks on time, while independence is reflected in their initiative to learn, self-confidence, and time management skills. However, there are still challenges such as differences in students’ abilities, reliance on teachers or peers, and a lack of parental support.